AVOIDING SURGERY DAY CANCELLATION BY FINDING PREVENTABLE CAUSES – A TWO YEARS EXPERIENCE - Ahmad, Maqsood; Akmal, Muhammad; Khurshid, Tassadaq; Saleem, Amer; Haq, Inam Ul; Syed, Fatimah Tassadaq (Pakistan Armed Forces Medical Journal, 2021)
Objective: To present 2 years’ experience of working at operating room Armed Forces Institute of Urology finding the causes for surgery cancellation.Study Design: Retrospective observational study.Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi, from Sep 2016 to Sep 2018.Methodology: The authors retrospectively reviewed operation theatre record of two years finding all cancelled cases. The cases cancelled on each operation day were enlisted for the study while entering the cause of negation. The factors contributing cancellation were separated to patient related and hospital related. These hospital and patient related factors were further divided into avoidable or unavoidable category. “Avoidable” was defined as a cancellation due to circumstances or information that existed prior to the day of surgery and could have been avoided with adequate review or communication by the medical staff before the date of surgery and can be prevented by preemptively addressing the components contributing to cancellation. Similarly unavoidable factors are those factors which are beyond human control and cannot be eliminated but reduced to minimum.Results: A total of 584/10,000 (5.84%) cases were cancelled on the day of surgery. Avoidable cancellations were found in 359 (61.5%) cases versus 225 (38.5%) of unavoidable causes. Of the avoidable cancellations, 18% were hospital related versus 43% were patient related causes. Of the avoidable, hospital related cancellations, the most common event were related to poor preparation of the patient, scheduling error and poor surgical decision. The unavoidable hospital related causes were 65 (11%) versus patient related 160 (27%).Conclusions: A thorough pre anesthetic checkup, optimization of concurrent conditions and discussing next day operation list may minimize the surgery cancellation rate.